2001
DOI: 10.1006/viro.2001.0855
|View full text |Cite
|
Sign up to set email alerts
|

Rack1 Binds HIV-1 Nef and Can Act as a Nef–Protein Kinase C Adaptor

Abstract: Nef proteins of primate immunodeficiency viruses exert pleiotropic effects, such as enhanced endocytosis of CD4 and MHC-I cell surface molecules, perturbation of signal transduction cascades, and virion infectivity enhancement. Nef function intersects that of a number of cell kinases, including C kinases (PKCs) and Src-family kinases. Here the interaction of HIV-1 Nef with Rack1 (receptor for activated C kinase 1) is reported. Nef binds the Rack1 C-terminal moiety in a yeast two-hybrid system and in cell-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…Therefore, we postulate that the interaction takes place at sorting endosomes or at subdomains in the plasma membrane (e.g. clathrin-coated pits, where RACK1 was previously reported to localize in HEK-293 cells) (34).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, we postulate that the interaction takes place at sorting endosomes or at subdomains in the plasma membrane (e.g. clathrin-coated pits, where RACK1 was previously reported to localize in HEK-293 cells) (34).…”
Section: Discussionmentioning
confidence: 93%
“…Interaction of NHE9 with RACK1 Is Topologically Possible-RACK1 is localized to the cytoplasm (31)(32)(33)(34)(35)(36)(37). Therefore, interaction with NHE9 would be possible only if the C terminus of NHE9 is exposed to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because this region is sufficient for binding, it is conceivable that folding of RACK1 into a complete seven-bladed-propeller structure is not essential for its association with FAN. The very same region of RACK1 has also been implicated in its binding to the integrin ␤ subunit and to the HIV-1 Nef protein as well as to the cAMP-specific phosphodiesterase isoform PDE4D5 (23,33,55). Obviously, this region constitutes an interface through which RACK1 can interact with various different proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al reported that A73 protein translated from CST (BART BARF0) transcript RNA of EpsteinBarr virus is able to interact with cellular RACK1 and modulate signaling from protein kinase C and Src tyrosine kinase to regulate cancer growth, such as nasopharyngeal carcinoma (19). It has also been noted that RACK1 acts as a human immunodeficiency virus Nef intracellular docking site, bringing Nef and protein kinase C together (a Nef-protein kinase C adaptor) (8). Sang et al demonstrated that RACK1 physically interacts with adenovirus E1A and acts as a repressor of E1A, possibly by antagonizing the effects of E1A on host gene transcription (18).…”
Section: Discussionmentioning
confidence: 99%